Antecedents of organisational creativity: a multi-level approach - Gupta, Ritu; Banerjee, Pratyush (Business: Theory and Practice, 2016)
The purpose of this literature review is to provide a better understanding of the antecedents of organisational creativity with a multi-level approach. Organisational creativity is a sum total of the creativity accounted for by the individual employees of the organisation, the cumulative creativity of a team or group and creativity arising out of different structural components of an organisation. Some of the antecedents identified from the literature include personality, intrinsic motivation, group cohesion, social inhibition, cognitive interference, leader member exchange, organisational culture and climate, amongst others at individual, group and organisational level. Based on the literature review, suggestions for future research and research propositions have been proposed.